HUBUNGAN PENGGUNAAN MEDIA SOSIAL TERHADAP INTERAKSI SOSIAL REMAJA - Lisa Andriani; Safri Safri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Social media is a media that makes it easy for someone to socialize easily and quickly. Excessive used of social media has an impact in social interactions, expecially adolescent. The purpose of this study was to find out the relationship between the use of social media and adolescent social interaction. This study uses a quantitative design with cross sectional design. This research was conducted on VIII grade junior high school adolescent at Pekanbaru 9 Junior High School to 198 respondents who selected using the Random Sampling. The measuring instrument used is a valid and reliable questionnaire. The analysis used was univariate analiysis and bivariate analysis with the chi-square test. The result of this study indicate that there is a relations between the use of social media with adolescent social interaction with p value 0,000 (α 0,05), so that it can be concluded the usof social media influences the social interaction in adolescent in 9 junior higt school in Pekanbaru. This research is expected to be one of the information for students, parents and schools to find out the positive and negative effects of using social media on adolescent social interactions. Keyword: Social Interactions, Social Media, Teenager